Are Cash Transfers Made to Women Spent Like Other Sources of Income? - Schady, Norbert; Rosero, Jose (2012)
We use a randomized design to analyze the effects of unconditional cash transfers to women on the food Engel curve. After the intervention, households assigned to the "treatment" group had significantly higher food shares than those assigned to the "control" group.